Telocytes in human isolated atrial amyloidosis: ultrastructural remodelling - Mandache, E.; Gherghiceanu, M.; Macarie, C.; Kostin, S.; Popescu, L. M. (Journal of cellular and molecular medicine, 2010)
The human heart can be frequently affected by an organ‐limited amyloidosis called isolated atrial amyloidosis (IAA). IAA is a frequent histopathological finding in patients with long‐standing atrial fibrillation (AF). The aim of this paper was to investigate the ultrastructure of cardiomyocytes and telocytes in patients with AF and IAA. Human atrial biopsies were obtained from 37 patients undergoing cardiac surgery, 23 having AF (62%). Small fragments were harvested from the left and right atrial appendages and from the atrial sleeves of pulmonary veins and processed for electron microscopy (EM). Additional fragments were paraffin embedded for Congo‐red staining. The EM examination certified that 17 patients had IAA and 82% of them had AF. EM showed that amyloid deposits, composed of characteristic 10‐nm‐thick filaments were strictly extra‐cellular. Although, under light microscope some amyloid deposits seemed to be located within the cardiomyocyte cytoplasm, EM showed that these deposits are actually located in interstitial recesses. Moreover, EM revealed that telopodes, the long and slender processes of telocytes, usually surround the amyloid deposits limiting their spreading into the interstitium. Our results come to endorse the presumptive association of AF and IAA, and show the exclusive, extracellular localization of amyloid fibrils. The particular connection of telopodes with amyloid deposits suggests their involvement in isolated atrial amyloidosis and AF pathogenesis.